(3GdJPjjd hGdJcejd aj TQM cJGH GdJSgjds - (3eMeO Hf jhSa Hf Ydj Hf jhSa GHf nMnqjGf GdZQfGWj GdCfOdSj GdLjGfj, GdpqfraRj, CKjQ GdOjf, CHh MjGf,J (B745 (3g` s ((3eMeO Hf EHQGgje Hf Ydi Hf YHO GdfhQ s)
(3ChdgG (B:s
(3jHOC HHGH MQha GdLQ s
(3BNQgG (B:s
(3ShGA CcGf GdSGcf dg UhQI ai GdNW ceG eKdfG Ce djSJ dg UhQI hgh GdJfhjf , fMh NHjKI GLJKJ bQF HVe GdJfhje hcSQg ced GdSaQ GdQGHY ef GdJPjjd hGdJcejd s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B152 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B130s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdfMhs